Understanding the Reasons for Non-Adoption of Internet Banking - P. Praveen Kumar, Dr.; K. C. Raja Shree, Ms. (International Journal of Engineering and Technology, 2018)
In the recent years, Internet Banking (IB) acts as a popular mode of payments. The adoption rate of IB is significantly increasing in India among mature consumers. This study primarily aims to measure the level of awareness about different features of internet banking and various reasons for non-adoption of IB. Furthermore, this proposed study attempts to measure the relationship between personal profile and reasons for non-adoption of IB. Data has been grabbed through questionnaire. The respondents are professional students who pursue their professional degree in Chennai. This study finds that students possess knowledge about various features of IB. Due to lack of personal touch, students are not adopting IB. There is a relationship between personal profile of students and their reasons for non-adoption.Â Â Â Â Â Â Â Â